2019
DOI: 10.1088/1757-899x/551/1/012079
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Crumb Rubber Loading on the Properties of Fly Ash-Based Geopolymer Concrete

Abstract: This study aims at viability study the effects of addition of crumb rubber loading in fly ash-based geopolymer concrete for its properties. Crumb rubber is the recycled rubber from automotive scrap tires which can reduce scrap into uniform granules shapes that can absorb stress that reduces the reflective cracking because of its elastic properties. Geopolymer concrete includes an alternate material i.e Fly ash in replacement of cement, as a binding material. Mortar cubes of size 50mm x 50mm x 50mm were casted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…The aggregates used for the study include fine and coarse natural aggregates classified based on size. Table 2 shows that except Azmi et al [40], most research used river sand as fine aggregates. RuGPC is made using a range of coarse aggregates, including crushed basalt [28], crushed dolomite [19], and crushed gravel [17,38].…”
Section: Constituents Of Rugpcmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggregates used for the study include fine and coarse natural aggregates classified based on size. Table 2 shows that except Azmi et al [40], most research used river sand as fine aggregates. RuGPC is made using a range of coarse aggregates, including crushed basalt [28], crushed dolomite [19], and crushed gravel [17,38].…”
Section: Constituents Of Rugpcmentioning
confidence: 99%
“…The specimens fail quite soon resulting from the cracks quickly developing around the rubber particles while loading IOP Publishing doi:10.1088/1755-1315/1149/1/012009 8 [5]. When rubber particles and geopolymer paste are not properly bonded, applied forces are not distributed evenly, which can cause cracks [5,20,40]. Another reason for lower compressive strength is rubber's susceptibility to rising during vibration as a result of its low specific gravity and deficiency of adhesion to other concrete components, which results in the top layer having a larger concentration of rubber ending up in a non-homogeneous concrete [5,42].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…It can be concluded that the waterabsorption capacity of rubberized geopolymer concrete increases with increasing crumb rubber content. This is because the number and size of voids in the geopolymeric concrete microstructure increased [48]. The evaporation of water content and the lower degree of mix compaction due to the light weight of rubber lead to the formation of more voids in the interfacial transition zone between the geopolymer matrix and the rubber waste aggregate compared with the geopolymer concrete mix not containing crumbed rubber waste aggregate.…”
Section: Water Absorptionmentioning
confidence: 99%
“…[106], yet the majority of studies adopted a ratio between 1.5 and 2.5 [6,7,12,20,54,72,76,96]. Besides the molarity of NaOH solution and Na2SiO3/NaOH ratio, GeoPC is affected by the ratio of alkaline activator-toaluminosilicate precursor which, as indicated in Table 1, varied in RuG studies between 0.152 [65] and 0.85 [73], with an optimum value of 0.4 [6,7,12,20,72,96,107].…”
Section: Alkaline Solutionsmentioning
confidence: 99%